Criminology and Crime Science: a Review on the Crime Prevention and Suppression for the Tourist Industry Between Thailand and Malaysia - Hakparn, Surachate; Lertbunchardwong, Kanittha; Potikengrith, Tepvisit; Ekhwan Toriman, Mohd (International Journal of Engineering and Technology, 2018)
The travel and tourism industry situation between Thailand and Malaysia is being threatened by crime as well as exploits tourists and safety in life and property. The tourism industry has declined, affecting both countries and their economies. Present to delineate crime prevention for the tourist industry in Thailand and Malaysia and develop the collaboration within performing such scheme. Qualitative approach through documentary research, focus group and in-depth interview were the data collecting. The data used thirty criminal justice stakeholders from both countries. The both countries had provided the policy to contribute the tourist industry as well as exchange the tourist more increasing, including the foreigners tourists intended to visit the both countries. They collaborated in several term for the tourists safety and other good relations. Crime protection and destruction for the tourist Industry between Thailand and Malaysia. They are together common policy setting as well as collaboration related the tourist industry. Including, the upgrading and improvements needed in the dimensions such as provision of facility components, facilities, available services and infrastructure. Â Â